The Acceptance and Commitment Therapy (ACT) Reduce Stress in Patients With Type 2 Diabetes Mellitus - Bistara, Difran Nobel; Susanti, Susanti; Pranata, Satriya; Mustamu, Alva Cherry (Scripta Medica, 2023)
Background/Aimː Diabetes mellitus patients may be more vulnerable to stress due to the requirement for lifestyle changes and blood sugar management. Stress occurs when people sense a mismatch between their available resources and the expectations put on them, especially when the expectations are believed to be excessive in comparison to the preceding circumstance. The purpose of this study is to look at the effectiveness of the acceptance and commitment therapy (ACT) as a stress-reduction intervention in patients with type 2 diabetes mellitus (T2DM) by enhancing their psychological well-being.Methodsː A total of 40 people were allocated to either the intervention or control groups at random. The intervention group got counselling on the pillars of diabetes control, followed by a stress level pre-test. Following that, the ACT intervention was carried out. After completing the post-test, the control group got the same intervention. The ACT module and a questionnaire to evaluate stress levels in T2DM patients were used in this study. Resultsː Following the ACT session, the measuring findings for stress levels in the intervention group showed a reduction. Both the intervention and control groups saw stress reduction; however, the intervention group had a greater reduction.Conclusionsː The ACT intervention reduced stress levels in the intervention group. ACT appeared as the variable having the largest effect on lowering stress levels after taking into account variables such as duration of suffering, education, sex and age-related to T2DM.
Keywords: Stress levels; Type 2 diabetes mellitus; Acceptance and commitment therapy